Medium Term Economic Effects of Peak Oil Today - Ulrike Lehr; Christian Lutz; Kirsten Wiebe (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2011)
The paper at hand presents results of a model-based scenario analysis on the economic implications in the next decade of an oil peak today and significantly decreasing oil production in the coming years. For that the extraction paths of oil and other fossil fuels given in LBST (2010) are implemented in the global macroeconomic model GINFORS. Additionally, the scenarios incorporate different technological potentials for energy efficiency and renewable energy, which cannot be forecast using econometric methods. GINFORS then endogenously determines world-wide energy demand and energy prices.The results show that the oil shortage firstly and strongly affects the transport sector but then has indirect effects on all other sectors through global supply chains. The medium term reactions to the oil shortage and corresponding substantial increase in the oil price of the global energy system and the individual sectors are energy saving and substitution, lowering global energy demand. The global macroeconomic effects of an increase of the oil price as high as modelled here are comparable to the effects of the financial and economic crises of 2008/2009.
Keywords: Q32; 330; oil peak today; model-based scenario analysis; world-wide energy demand; energy prices; Ölpreis; Ölpreis; Makroökonomischer Einfluss; Welt